703 A trans-generation conundrum with implications in rehabilitation programs – what factors influence non-specific back pain in children? (Balneo and PRM Research Journal, 2024)
Back pain in children and adolescents is one of the most frequent reasons for seeing a medical specialist worldwide. Many factors have been incriminated when it comes to influencing the appearance of non-specific back pain in children as well as in adults. For the younger population, some of the culprits seem to be sitting for long periods, us-ing harmful postural patterns, a forward head posture determined by incorrect positioning during prolonged studying hours, and carrying a too-heavy backpack, but do they really influence non-specific back pain in children? These ques-tions are valid for all generations and countries.This paper aimed to review the published literature to determine whether the factors mentioned above, sitting in mismatched school furniture, carrying heavy backpacks, and forward head posture, influence the incidence of non-specific back pain in children and whether there are any data or differences between the general population and Roma-nian students. For this purpose, we conducted database research using the keywords “non-specific back pain in chil-dren, sitting, school furniture, forward head posture, backpack carrying” and various combinations of these terms, which returned 37 eligible articles for this paper in PubMed - Center for Biotechnology Information (NCBI) and Sci-enceDirect. There was no time limit on the researched articles, and they had to refer to the pediatric population, be open-access and in extenso articles, and be written in English, French, or Spanish.After analyzing the results from these articles, the conclusion is that there is no evident or spe-cific connection between non-specific back pain in pediatric populations and harmful posture patterns while sitting or carrying a backpack. Also, more multicentered research using fewer variables and more objective measurement instruments is needed.